Detection of Borrelia burgdorferi sensu stricto and Borrelia garinii DNAs in patient with Hyperkeratosis lenticularis perstans (Flegel disease) - Schwarzova, Katarina; Kozub, Peter; Szep, Zoltan; Golovchenko, Marina; Rudenko, Natasha (Folia microbiologica, 2016)
Determination of the causative agent of erythema-like skin lesions in case of nonspecific superficial perivascular dermatitis was supported by histological examination and led to the latter diagnosis of Hyperkeratosis lenticularis perstans (Flegel disease) in patient. The presence of antibodies against Borrelia burgdorferi in patient serum was confirmed by a routine ELISA method and verified by Western blot technique. Skin biopsy and blood specimens were analyzed by PCR and multilocus sequence analysis (MLSA). Western blot method revealed IgG antibody response against two specific antigens, 17 and 83 kDa proteins. The recombinant test detected IgG antibody response against p100 and p41 antigens. The sequence analysis of amplicons from the selected genomic loci obtained from skin biopsy and serum samples revealed the presence of two species from B. burgdorferi sensu lato complex as a co-infection in this patient-B. burgdorferi sensu stricto (s.s.) and Borrelia garinii.
Keywords: Multilocus Sequence Typing; Antibodies, Bacterial; Borrelia burgdorferi komplex; keratóza; biopsie; imunoglobulin G; lidé; lidé středního věku; western blotting; kůže; Humans; antigeny bakteriální; protilátky bakteriální; Middle Aged; Coinfection; koinfekce; Keratosis; Antigens, Bacterial; DNA bakterií; multilokusová sekvenční typizace; polymerázová řetězová reakce; Immunoglobulin G; Biopsy; Polymerase Chain Reaction; DNA, Bacterial; ženské pohlaví; Borrelia burgdorferi; Borrelia burgdorferi Group; Female; Blotting, Western; Skin